Education : an investment or a liability? : an economic analysis of education and its role in the development of underdeveloped countries, with special reference to the concept of human capital - Bates, Terrence (Rhodes University, Faculty of Commerce, Department of Economics, 1970)
From Introduction: Education, in the broadest sense of the term, is as old as man himself, but the attention devoted to it has fluctuated to extremities over time. The "Economics of Education", as a separate study, has suffered the same cyclical life, but has in recent years experienced a prolonged revival of interest, eapecially with regard to the concept of "Human Capital".
Keywords: Education -- Economic aspects -- Developing countries; Human capital